Module Development Based On Picture Stories To Improve Interest In Learning Material Environmental Pollution - Tety Eka Nur Yuliana; Sri Wahyuni; Rayendra Wahyu Bachtiar (Pancaran Pendidikan, 2017)
It is widely acknowledged that the use of picture stories supports the improved study interest of students. Interest or high desire in learning is necessary because if the learning without the strong will, then the job was not getting good results. But teaching materials that have many pictures have not been used in schools. The aim of this research is to know the validity, practicality, and effectiveness of module based on picture stories to improve study interest of the student in the material environmental pollution. The type of this research is a development research which applies a 4D model of Thiagarajan et al. 4D model consists of four steps, but in this research only limited on the third step. The results showed that validity of the module is valid, enforceability value indicates that the module is practical to be used, and it is also effective to improve student's interest in environmental pollution material.